Phase II Trial of Erlotinib Plus Gemcitabine Chemotherapy in Korean Patients with Advanced Pancreatic Cancer and Prognostic Factors for Chemotherapeutic Response - Park, Semi; Chung, Moon Jae; Park, Jeong Youp; Chung, Jae Bock; Bang, Seungmin; Park, Seung Woo; Song, Si Young (Gut and liver, 2013)
Erlotinib and gemcitabine combined chemotherapy is becoming the treatment of choice in advanced pancreatic cancer. We evaluated the effectiveness of treatment with erlotinib plus gemcitabine and the prognostic factors for chemotherapeutic response in Korean pancreatic cancer patients. Sixty-nine patients with advanced pancreatic cancer who were treated with daily erlotinib 100 mg orally and gemcitabine 1,000 mg/m(2)/30 min intravenous infusion on days 1, 8, and 15 of each 4-week cycle from 2006 to 2009 were included in this study. This study was a phase II single-center trial. All 69 patients with advanced pancreatic cancer were chemotherapy-naïve. The objective response rate was 18.8%, and the overall tumor-stabilization rate was 49.2%. The median overall survival was 7.7 months (95% confidence interval [CI], 6.0 to 9.4 months). The median progression-free survival was 1.9 months (95% CI, 1.4 to 2.5 months). Prognostic factors for good chemotherapeutic response were good performance status and the presence of skin rash during chemotherapy. Patients with lower performance scores showed worse chemotherapeutic responses (odds ratio [OR], 7.6; 95% CI, 2.4 to 24.8). Poor responses were predicted by the absence of skin rash during chemotherapy (OR, 3.0; 95% CI, 1.4 to 6.3). Erlotinib and gemcitabine chemotherapy is a tolerable treatment regimen and has a favorable therapeutic effect in Korean patients with advanced pancreatic cancer.